Peaceful schools - Lubelska, Anna (International journal of children's spirituality, 2012)
This article is based on the presentation Anna Lubelska made at the 12th International Conference on Children’s Spirituality. Anna is Director of Spiritual England which is a not for profit organisation set up in 2009. Its aim is to promote the importance of spirituality and to help increase access to opportunities for spiritual development. Its remit covers spirituality in all faiths and no faith. Anna worked for many years in community development and services for children and families. This year she started the Peaceful Schools Movement which encourages schools to become more peaceful. For example, schools are enabled to engage creatively with their pupils to design quiet rooms and gardens, alongside undertaking activities such as the practice of mindfulness and training in conflict resolution, all within the context of a whole-school ethos of dynamic peacefulness.